The Effect of Spiritual Motivation, Spiritual and Intellectual Intelligence on Religious Performance Mediated by Job Satisfaction - Hussein , Amir; Wibisono, Chablullah; Wijaya, Dicky; Gratitude, Ihram Bani (International Journal of Advances in Social Sciences and Humanities, 2022)
Today, universities have a significant role in developing human resources, knowledge and technology and driving a dynamic society. The lecturers are essential in teaching, training and educating tasks for students. Thus, this study examines the effect of spiritual motivation and spiritual and intellectual intelligence on religious performance mediated by job satisfaction at STAI Batam, Riau, Indonesia. The design of this study is a quantitative approach through a survey questionnaire. A total of 160 lecturers from the Islamic High School in the Riau Archipelago participated in this study and collected using purposive sampling started September until November 2021. The data were analyzed using the Structural Equation Model – Analysis of Moments Structures (SEM-AMOS). The result indicated that spiritual motivation is positively related to religious performance. Spiritual Intelligence and Intellectual Intelligence are not significantly related to religious performance. Also, job satisfaction mediates the relationship between spiritual and intellectual intelligence on religious performance. In conclusion, this study has identified the determinant factors of religious performance. In Islam, motivation is crucial in interpreting and giving birth to human actions. In the Islamic concept, the role of motivation is called intention and worship. The intention is a key driver of man to do or charity, while worship is the goal of human acts or deeds.